The impacts of supply chain linkages on micro and small scale enterprises' performance in Sarawak - Siti Aisyah binti Ya'kob (Kulliyyah of Economics and Management SciencesInternational islamic University Malaysia, 2014)
Supply chain linkage is an important aspect in supply chain relationship which involves cost, risks and challenges to enterprises. The improvement on supply chain linkages could be measured based on monetary and non-monetary performance. The objective of this study is to predict the relationship between information sharing, development programme, and outsourcing on performance of micro and small enterprises. Another purpose of this study is to identify the most important factor that affects the business performance. This study invited 350 micro and small enterprises in Kuching city to participate in the survey. In total, only 214 sets of questionnaire are usable for the analysis. Descriptive analysis, normality testing, factor analysis, reliability, t-test, correlation and multiple regression analysis are tested in this study. The findings are consistent with prior literature that information sharing and development programme have positive and significant relationship with business performance. Outsourcing has positive impact on business performance but this study fails to prove the presence of significant relationship between these two factors. Furthermore, the result shows that the development programme factor is the most important factor that affects the business performance. Using multiple regression analysis, it can be concluded that the supply chain linkages cause direct impact on business performance. As the implications, the benefits of supply chain linkage are foreseen i.e. to encourage accurate, complete, sufficient and reliable information sharing between channel members; participate in the channel members' activities; confirm the purposes of outsourcing.